Education is the priority factor of the country's development. - Ruziev Bobosher Usarovich (Peerian Journals Publishing, 2023)
Reforms in the field of education are one of the important priorities of any country. In the field of higher education, entering the list of the best universities in the world ranking is an important factor of the each country's socioeconomic development. The article discusses the fact that the reform of the education system is the main basis of social development.
Keywords: Higher education; jadidism; world rating